2021
DOI: 10.1128/mbio.00502-21
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of Lipopolysaccharide Signaling in Gingival Keratinocytes via MCPIP-1 Degradation as a Novel Pathogenic Strategy of Inflammophilic Pathobionts

Abstract: Periodontitis is a highly prevalent disease caused by accumulation of a bacterial biofilm. Periodontal pathogens use a number of virulence strategies that are under intensive study to find optimal therapeutic approaches against bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Substrate hydrolysis was measured at 405 nm for 40 min, and activity was presented as milli-optical density units per minute per microliter of sample. Before stimulation of eucaryotic cells, enzymes were activated with 10 mM l -cysteine as described recently ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Substrate hydrolysis was measured at 405 nm for 40 min, and activity was presented as milli-optical density units per minute per microliter of sample. Before stimulation of eucaryotic cells, enzymes were activated with 10 mM l -cysteine as described recently ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of OMVs was performed as described previously ( 10 , 11 ). Bacterial suspensions (OD 600 of 1) were sonicated for 90 s in a water bath to increase the release of OMVs from the bacterial surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocyte chemoattractant protein‐induced protein‐1 (MCPIP‐1), also called Regnase‐1, is a host inflammatory response cytokine RNase 9 . It was recently demonstrated that P. gingivalis can degrade MCPIP‐1 by its gingipains, which leads to the overactivation of the NF‐κB signaling pathway and increase the transcripts of proinflammatory cytokines 10 . MCPIP‐1 acts as a broad suppressor of miRNA activity and biogenesis 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, suppression of MALT‐1 increases MCPIP‐1 activity 17 . It was hypothesized that MCPIP‐1 depletion in periodontitis can be an outcome of MALT‐1 activation, however, this was not yet proven 10 . Indeed, simultaneous regulations of MCPIP‐1 and MALT‐1 gene and protein expressions by periodontitis‐associated bacteria and inflammatory mediators have not been elucidated as well.…”
Section: Introductionmentioning
confidence: 99%